Identification and validation of ATP6V1G1-regulated phosphorylated proteins in hepatocellular carcinoma. - Yi Zhang; Liuyi Lu; Mingxing Chen; Jiaqi Nie; Xue Qin; Huaping Chen (PLoS ONE)
V-ATPase Subunit G1 (ATP6V1G1) is one of the subunits of Vacuolar ATPases. Previous studies have indicated that ATP6V1G1 plays important roles in hepatocellular carcinoma (HCC) and is associated with HCC progression. However, the effect of ATP6V1G1 in HCC requires further elucidation. The aim of the present study was to explore the roles of ATP6V1G1 in HCC and further decipher the detailed mechanism. To identify the phosphorylated proteins regulated by ATP6V1G1 in HCC, phosphoproteomics and LC-MS/MS analysis were performed on HepG2 with overexpression of ATP6V1G1 and empty vector. Western blotting was applied to validate the differentially expressed phosphorylated proteins (DEPPs). As a result, 163 DEPPs were identified by proteomics; two up-regulated phosphorylated proteins (p-RPS6(Ser235)) and (p-SQSTM1(Ser272)) and two down-regulated phosphorylated proteins (p-PDPK1(Ser241)) and (p-EEF2 (Ser57)) were validated. Taken together, this study highlighted the potential impact of ATP6V1G1 on tumor progression, which may be beneficial to liver cancer related basic research.